The Relationship Between Knowledge and Physical Activity with Blood Glucose Levels in Patients with Diabetes Mellitus: Knowledge, Physical Activity, and Blood Glucose in Diabetes - Hasni Hasni; Sonya Beljeur (CV. Paperhome Indonesia, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia and remains a major global health problem. Effective management of DM requires proper self-management behaviors, including adequate knowledge and regular physical activity, which are essential for maintaining optimal blood glucose levels. This study aimed to examine the relationship between knowledge and physical activity with blood glucose levels among patients with diabetes mellitus. Methods: This study employed a quantitative approach with a descriptive correlational design using a cross-sectional method. The study was conducted at Tadjuddin Chalid Hospital, Makassar, Indonesia, in December 2025. A total of 40 respondents were selected using purposive sampling. Data were collected using structured questionnaires, while blood glucose data were obtained from medical records. Data were analyzed using descriptive statistics and Chi-square. Result: The results showed that the majority of respondents were aged 50–60 years (57.5%), female (67.5%), had low educational levels (87.5%), and had been living with diabetes for 4–6 years (52.5%). Most respondents had blood glucose levels of 100–200 mg/dL (62.5%). There was a statistically significant relationship between knowledge and blood glucose levels (p = 0.000), where respondents with good knowledge had better glycemic control. Additionally, a significant relationship was found between physical activity and blood glucose levels (p = 0.000), indicating that respondents with active physical activity had better glycemic control compared to those with low physical activity. Conclusion: Knowledge and physical activity are significant determinants of glycemic control among patients with diabetes mellitus. Therefore, integrating patient education and the promotion of regular physical activity into diabetes management programs is essential to improve clinical outcomes and reduce the risk of complications.